Realization of the Pentahelix Model in the Development of Paksebali Tourism Village Towards Sustainable Tourism - Cahyani, Ni Komang Rida; Widhiasthini, Ni Wayan; Yulyana Dewi, Ni Luh; Widhi Antari, Ni Putu Bayu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the implementation of the pentahelix model in the development of Paksebali Tourism Village toward sustainable tourism in Klungkung Regency. Using a qualitative approach, data were collected through in-depth interviews with government officials, academics, business actors, tourism group (Pokdarwis) managers, and community members, supported by field observations and documentation studies. The data were analyzed using inductive thematic coding to identify collaboration patterns, actor roles, and key challenges. The findings show that the government functions as a regulator and facilitator through policy support, infrastructure development, and capacity-building programs, although coordination between agencies remains inconsistent. Academic involvement contributes to potential mapping and community mentoring but is generally short-term and lacks continuity. Business actors strengthen the tourism economy but tend to work independently, resulting in limited integration with village development plans. The community becomes the core driver of attractions and tourism activities, yet still faces obstacles in service standards, digital literacy, and human resource capacity. The media element shows the weakest performance, with limited digital promotion and minimal collaboration with external media partners. Overall, the realization of the pentahelix model in Paksebali has begun but is not yet optimal. Strengthening coordination mechanisms, sustaining programs, enhancing digital promotion, and improving stakeholder synergy are essential to support sustainable tourism development.